2020
DOI: 10.5194/tc-14-1273-2020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water percolation through crevasses on the thermal regime of a Himalayan mountain glacier

Abstract: Abstract. In cold and arid climates, small glaciers with cold accumulation zones are often thought to be entirely cold based. However, scattering in ground-penetrating radar (GPR) measurements on the Rikha Samba Glacier in the Nepal Himalayas suggests a large amount of temperate ice that seems to be influenced by the presence of crevassed areas. We used a coupled thermo-mechanical model forced by a firn model accounting for firn heating to interpret the observed thermal regime. Using a simple energy conservati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Crevasses have been shown to be able to cause a cycle of positive feedbacks in glacier dynamics by increasing surface melt-water input to the glacier bed, a feedback that was documented in detail during the surge on Basin-3 of Austfonna (Dunse and others, 2015), and has been observed on other glaciers (e.g. Gilbert and others, 2020). Because the accelerating destabilization prior to the active surge probably only lasts for a few seasons on Svalbard tidewater glaciers, high temporal resolution analysis is necessary to understand both how the destabilization begins and further evolves.…”
Section: Introductionmentioning
confidence: 91%
“…Crevasses have been shown to be able to cause a cycle of positive feedbacks in glacier dynamics by increasing surface melt-water input to the glacier bed, a feedback that was documented in detail during the surge on Basin-3 of Austfonna (Dunse and others, 2015), and has been observed on other glaciers (e.g. Gilbert and others, 2020). Because the accelerating destabilization prior to the active surge probably only lasts for a few seasons on Svalbard tidewater glaciers, high temporal resolution analysis is necessary to understand both how the destabilization begins and further evolves.…”
Section: Introductionmentioning
confidence: 91%
“…Here, it was considered that the crevasses, which possibly initiated in association with band ogives several kilometers upglacier, may have warmed the glacier's full thickness of ∼250-300 m. Such inferences are not limited to the margins of the GrIS. For example, Gilbert et al (2020) suggested that meltwater refreezing in crevasses may be responsible for deep warming, inferred from surface ground-penetrating radar, at Rikha Samba Glacier, Nepal, a process that may also contribute to anomalously warm englacial ice measured in boreholes across the debris-covered tongue of Khumbu Glacier, Nepal (Miles et al, 2018). Second, deep englacially terminating crevasses have also been invoked to explain englacial radar scattering.…”
mentioning
confidence: 99%
“…For example, heat fluxes driven by meltwater conveyance to the englacial and subglacial environments of debris-covered glaciers (i.e. cryo-hydrologic warming (Gilbert et al, 2020;Phillips et al, 2010)), could be explored using numerical models guided by field-based measurements of supraglacial water fluxes and temperatures, along with geophysical and/or borehole-based investigations of englacial temperature fields. Specific loci and timescales of meltwater routing, storage, and release should be determined.…”
Section: Understanding Hydrological Processes Influencing Glacier Mass Balancementioning
confidence: 99%